2018
DOI: 10.1155/2018/9856910
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Antibodies against Extractable Nuclear Antigens, Antinuclear Antibodies, and Autoimmune Diseases in a Brazilian Public Hospital

Abstract: One characteristic of autoimmune diseases (ADs) is the production of autoantibodies for extractable nuclear autoantigens, which may aid in the discrimination of the different types of autoimmune diseases and is related to different antinuclear antibody (ANA) patterns. The present study verified the profile of patient samples tested for extractable nuclear antigens (ENA) antibodies in a public hospital and correlated the ENA results with ANA patterns and patient diagnoses. The study reviewed data in the medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…In our study, the highest rate for nuclear speckled pattern-associated ANAs was found in anti-SS-A (48.1%), indicating a relatively moderate correlation. Consistent with previous studies, the agreement rate for speckled pattern-specific antibodies was higher than other ANAs [1,17,20]. Although anti-dsDNA and nucleosome were the most frequent antibodies in the homogeneous pattern, agreement rates were similar to the speckled pattern, and also had a high detection rate for anti-SS-A, anti-SS-B, anti-Ro-52, anti-Sm and anti-RNP/Sm.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the highest rate for nuclear speckled pattern-associated ANAs was found in anti-SS-A (48.1%), indicating a relatively moderate correlation. Consistent with previous studies, the agreement rate for speckled pattern-specific antibodies was higher than other ANAs [1,17,20]. Although anti-dsDNA and nucleosome were the most frequent antibodies in the homogeneous pattern, agreement rates were similar to the speckled pattern, and also had a high detection rate for anti-SS-A, anti-SS-B, anti-Ro-52, anti-Sm and anti-RNP/Sm.…”
Section: Discussionsupporting
confidence: 89%
“…As anti-RNP is a diagnostic marker for SLE and SSc and since a high level of anti-RNP is diagnostic of MCTD, this result could suggest the possibility of false positive cases according to clinical diagnoses, leading to misdiagnosis using the ELISA method 5. The problem of false-positive anti-ENA tests has been continuously raised, and it is recommended that testing be performed with two different methods to avoid false-positive results 2021. Clinical correlation with anti-ENA results can be another solution for avoiding false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…5 The problem of falsepositive anti-ENA tests has been continuously raised, and it is recommended that testing be performed with two different methods to avoid false-positive results. 20,21 Clinical correlation with anti-ENA results can be another solution for avoiding falsepositive results.…”
Section: Discussionmentioning
confidence: 99%
“…6 A study suggested that a combined detection of ANA and ENA autoantibodies was more helpful for the diagnosis and prognosis of AID. 7 The identification of ENAs plays a critical role in the diagnosis and management of ANAassociated rheumatic disease (AARD), such as systemic sclerosis (SSc), systemic lupus erythematosus (SLE), Sjogren's syndrome (SS), and mixed connective tissue disease (MCTD). [8][9][10] In addition, study suggests anti-SSA/Ro can be detected in the majority of SS patients (70%-100%) and 35% to 70% SLE patients, and anti-La/SSB is detectable in 45% of patients with SLE and up to 40% to 90% of patients with SS.…”
Section: Introductionmentioning
confidence: 99%